Weekly economic activity: Measurement and informational content - Philipp Wegmüller; Christian Glocker; Valentino Guggia (Austrian Institute of Economic Research (WIFO), 2021)
We construct a composite index to measure real activity of the Swiss economy on a weekly frequency. The index is based on a novel high-frequency data-set capturing economic activity across distinct dimensions over a long-time horizon. An adequate adjustment of raw data prior to deriving the latent factor is crucial for obtaining precise business cycle signals. By means of a real-time evaluation, we highlight the importance of our proposed adjustment procedure: first, our weekly index significantly outperforms a comparable index without adjusted input variables; secondly, the weekly index outperforms established monthly indicators in nowcasting GDP growth. These insights should help improve recently developed high-frequency indicators.
Keywords: C32; C38; C53; C55; E32; 330; Business cycle index; Dynamic factor model; High-frequency data; Nowcasting